Influence of coma aberration on aperture averaged scintillations in oceanic turbulence. (1st January 2018) - Luo, Yujuan; Ji, Xiaoling; Yu, Hong
Highlights: Method is proposed to reduce aperture averaged scintillations in weak oceanic turbulence. Aperture averaged scintillations can be suppressed using coma in weak oceanic turbulence. Aperture averaged scintillation isn't sensitive to coma in strong oceanic turbulence. Aperture averaged scintillation dominated by salinity-induced turbulence is large. Aperture averaged scintillation is suitable for characterizing coma beam scintillations. Abstract: The influence of coma aberration on aperture averaged scintillations in oceanic turbulence is studied in detail by using the numerical simulation method. In general, in weak oceanic turbulence, the aperture averaged scintillation can be effectively suppressed by means of the coma aberration, and the aperture averaged scintillation decreases as the coma aberration coefficient increases. However, in moderate and strong oceanic turbulence the influence of coma aberration on aperture averaged scintillations can be ignored. In addition, the aperture averaged scintillation dominated by salinity-induced turbulence is larger than that dominated by temperature-induced turbulence. In particular, it is shown that for coma-aberrated Gaussian beams, the behavior of aperture averaged scintillation index is quite different from the behavior of point scintillation index, and the aperture averaged scintillation index is more suitable for characterizing scintillations in practice.